Assessing international capital mobility in East Asian economies: a panel error-correction approach - Eng, Yoke Kee; Habibullah, Muzafar Shah (Routledge, 2006)
This study assesses financial integration and the degree of international capital mobility in the East Asian region by analyzing the dynamics of national saving-investment relationships. Following the work of Pelgrin & Schich (2004), we interpret the close relationship between national saving and investment in the long run reflecting a solvency constraint and focus on the short term saving investment analysis relationship to assess the degree of capital mobility. Applying the panel error -correction technique proposed by Pesaran et al. (1999), our empirical results suggest that there exists a long-run relationship between saving and investment and that the short-run is driven by the extent of the gap between current and long-run equilibrium values. The low estimated values of the short-run coefficient of the changes in the saving rate signal some degree of capital mobility.